2019
DOI: 10.1096/fj.201802226r
|View full text |Cite
|
Sign up to set email alerts
|

Tumoral microvesicle–activated glycometabolic reprogramming in fibroblasts promotes the progression of oral squamous cell carcinoma

Abstract: Metabolic reprogramming is a hallmark of cancer. Stromal cells could function as providers of energy metabolites for tumor cells by undergoing the “reverse Warburg effect,” but the mechanism has not been fully elucidated. The interaction between the tumoral microvesicles (TMVs) and stroma in the tumor microenvironment plays a critical role in facilitating cancer progression. In this study, we demonstrated a novel mechanism for the TMV‐mediated glycometabolic reprogramming of stromal cells. After being incubate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
65
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(68 citation statements)
references
References 49 publications
3
65
0
Order By: Relevance
“…Stimulation of fibroblasts with prostate cancer MV converted them to an activated phenotype and triggered the release of tumor-promoting fibroblast MV [48]. Similar observations were made in oral squamous carcinoma when normal human fibroblasts were treated with tumor-derived MV [49]. In this study, the switch to cancer-associated fibroblasts (CAF) was mainly mediated via metabolic reprogramming of the fibroblasts to aerobic glycolysis, with an increase in glucose uptake and lactate secretion.…”
Section: Role Of Cancer-associated MV and Their Protein Cargo In Tumosupporting
confidence: 68%
“…Stimulation of fibroblasts with prostate cancer MV converted them to an activated phenotype and triggered the release of tumor-promoting fibroblast MV [48]. Similar observations were made in oral squamous carcinoma when normal human fibroblasts were treated with tumor-derived MV [49]. In this study, the switch to cancer-associated fibroblasts (CAF) was mainly mediated via metabolic reprogramming of the fibroblasts to aerobic glycolysis, with an increase in glucose uptake and lactate secretion.…”
Section: Role Of Cancer-associated MV and Their Protein Cargo In Tumosupporting
confidence: 68%
“…Injection of a combination of untreated and TMV-treated HCFs with CAL-27 xenograft into nude mice found that treating with TMVs was associated with a significant increase in tumour weight (p < 0.05). The invasive potential of OSCC cells was demonstrated to be increased after being co-cultured with TMV-treated HCGs and partially reversed by knockdown of MCT1 in CaL-27 cells [23].…”
Section: Ev Mediated Fibroblast Interaction In Osccmentioning
confidence: 98%
“…Primary normal oral keratinocytes Exposure to OSCC-derived exosomes specifically modulated mRNA transcripts associated with matrix remodeling, cell cycle, differentiation, apoptosis, transcription and translation OSCC & Fibroblasts [33] OSCC line (HSC3) NOF HSC3-exosomes lead to uptake by NOFs with resulting upregulation of expression of non-coding RNA Lnc-CAF [23] OSCC line (Cal-27) HGFs (human gingival fibroblasts)…”
Section: Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Along with alterations in cancer cell metabolism, perturbations in the metabolism of tumor stroma are emerging as a key driver of metastatic progression. The interactions between cancer-associated fibroblasts, and tumor cells is described as a 'reverse Warburg effect' where cancer cells induce metabolic reprogramming of fibroblasts leading to increased aerobic glycolysis [67], as well as increased expression of monocarboxylate transporter-4 (MCT4) [68] resulting in release of lactate into the tumor microenvironment. This is correlated with upregulated expression of monocarboxylate transporter-1 (MCT1) mediated lactate uptake in cancer cells which has been shown to contribute to survival and growth [68], as well as tumor migration [69].…”
Section: Extracellular Roles Of Metabolic Enzymes In Metastasismentioning
confidence: 99%